Quality management in oil and gas projects - Rumane, Abdul Razzak (Boca Raton, FL : CRC Press/Taylor & Francis Group, LLC, 2021)
"This book provides the tools and techniques, management principles, procedures, concepts, and methods to ensure the successful completion of an oil and gas project and ensuring the proper design, procurement, and construction for making the project most qualitative, competitive, and economical for safer operational optimized performance. It discusses quality during design, selection of project teams, procurement procedure of EPC contract, managing quality during mobilization, procurement, execution, planning, scheduling, monitoring, control, quality, and testing to achieve the desired results for an oil and gas project. The book provides all the related information to professional practitioners, designers, consultants, contractors, quality managers, project managers, academics/instructors, involved in oil and gas projects, and related industries"--
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum engineering; Total quality management; BUSINESS & ECONOMICS / Purchasing & Buying; TECHNOLOGY / Manufacturing; BUSINESS & ECONOMICS / Industries / Manufacturing Industries